Pengaruh Pelatihan, Briefing, Dan Pengawasan Dalam Meningkatkan Kinerja Karyawan Outsourcing - Maya Ayu Sulistyowati; Dewi Andriani; Vera Firdaus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of training, briefing, and supervision in improving the performance of outsourced employees of PT. Karya Manunggal Jati both partially and simultaneously. The research method used is a quantitative method using a 1-5 Likert scale analysis tool which is then tested using SPSS 24 software. The data collection technique in this study used a questionnaire distributed via a google form link. The population in this study were 197 outsourced employees of group A PT Karya Manunggal Jati. The sampling method used was non probability sampling using purposive sampling, namely 116 male respondents. The results of this study indicate that training, briefing, and supervision partially and simultaneously have a positive and significant effect in improving the performance of outsourced employees of PT Karya Manunggal Jati. Keywords – Outsourced Employee Performance, Training, Briefing, Supervision